Peran Adopsi Teknologi Media Sosial terhadap Niat Berwirausaha Mahasiswa Rekayasa Politeknik Negeri Bandung - Abdul Malik Sayuti; Harmon Chaniago (Jurnal Riset Bisnis dan Investasi, 2020)
Social media among Politeknik Negeri Bandung (Polban) engineering students is commonly used in carrying out daily activities. It mostly related to students’s social activities. Social media among engineering students has not been aimed at supporting economic value activites such as entrepreneurship. In fact, students have been taken information technology and entrepereneurship courses during their study. This research aims to reveal the extent to which the adoption of social media technology by Polban engineering students affect on entrepreneurial intention. This research used a quantitaive approach by distributing 317 questionaires to Polban engineering students who met the criteria. Data were processed using multiple regression methods to see the influence’s size of adoption of social media technology on entrepreneurial intentions. The result of this research provide an up-to-date overview of effect of adoption of secial media technology in increasing the growth of entrepreneurial intention among Polban engineering students.